1998
DOI: 10.1021/bi985033u
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Crystal Structures of Δ5-3-Ketosteroid Isomerase with and without a Reaction Intermediate Analogue

Abstract: Equations 3b and 3c, which utilize abbreviations for terms in eq 3a, are correct as written. This error does not affect any of the data or conclusions in the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(82 citation statements)
references
References 0 publications
2
80
0
Order By: Relevance
“…[22][23][24][25][26] Structural comparisons with homologous proteins A structural similarity search using DALI 27 revealed that the LinA protomer was similar to α + β barrel fold proteins, with various functions listed in Table 1. [22][23][24][25][26][28][29][30][31][32][33][34] LinA shows low amino acid sequence identities (16% at the highest) with these structurally similar proteins. The quaternary structures of the α + β barrel fold proteins are varied: dimeric, trimeric, tetrameric, and tetradecameric.…”
Section: Resultsmentioning
confidence: 98%
“…[22][23][24][25][26] Structural comparisons with homologous proteins A structural similarity search using DALI 27 revealed that the LinA protomer was similar to α + β barrel fold proteins, with various functions listed in Table 1. [22][23][24][25][26][28][29][30][31][32][33][34] LinA shows low amino acid sequence identities (16% at the highest) with these structurally similar proteins. The quaternary structures of the α + β barrel fold proteins are varied: dimeric, trimeric, tetrameric, and tetradecameric.…”
Section: Resultsmentioning
confidence: 98%
“…The overall structure of ppKSI M105A is similar to that of wild-type ppKSI. Superimposing the coordinates of wild-type ppKSI (PDB entry 1OH0) 21 and ppKSI M105A (this work) yields an rmsd of 0.5 Å over 123 α-carbon atoms (Figure 3). …”
Section: Functional Site Prediction By Thematics and Poolmentioning
confidence: 88%
“…18 Like Bal32a, many aCb barrel fold proteins are dimeric, with the b-sheet forming the dimer interface. These close structural relatives of Bal32a include the enzymes ketosteroid isomerase (KSI), 19 nogalonic acid methyl ester cyclase (known as SnoaL) 20 and scytalone dehydratase (SD). 21 The overlay of Figure 2(d) emphasises the strong conservation across the family of bstrand elements forming the barrel scaffold, with most variations from Bal32a occurring at the top of the cone.…”
Section: Structural Homologs Of Bal32amentioning
confidence: 99%
“…In all these cases, a conserved bulky residue (most commonly aromatic) forms the bottom of the cavity, e.g. Tyr14 in KSI, 19 Trp31 in SD. 21 Bal32a differs considerably from its structural homologs in this region, with the equivalent position being occupied by Gly31.…”
Section: Structural Homologs Of Bal32amentioning
confidence: 99%
See 1 more Smart Citation